Validation of PELOD-2 score as a predictor of life-threatening organ dysfunction in pediatric sepsis - Yuyun Romaria Simanjuntak; Indra Saputra; Silvia Triratna; Achirul Bakri; Yulia Iriani (Indonesian Pediatric Society, 2020)
Background The Third International Consensus Definitions for Sepsis and Septic Shock (Sepsis-3) defined sepsis as life-threatening organ dysfunction due to immune dysregulation against infection. It recommends the Sequential (sepsis-related) Organ Failure Assessment (SOFA) score to evaluate life-threatening organ dysfunction. But the SOFA tool has not been adjusted for pediatric patients. The Indonesian Pediatrics Society (IPS) uses the same sepsis definition and recommends using the PELOD-2 score as an indicator of life-threatening organ dysfunction in children. Objective To evaluate the validity of the PELOD-2 score for predicting life-threatening organ dysfunction in pediatric sepsis. Methods A prospective cohort study was conducted in children with sepsis who were admitted to the PICU. Subjects were taken consecutively with inclusion criteria of 1 month-18 years of age, with organ dysfunction, having two or more symptoms of systemic inflammatory response syndrome (SIRS), and suspected or proven infection. PELOD-2 score, with and without lactate result, of each subject were plotted to receiver operating characteristic (ROC) curve, then we determined the most optimal cut off point to predict the life-threathneing organ dysfunction in pediatric sepsis based on the sensitivity and specificity of each score. Results Sixty-six patients were analyzed, with 40 males and 26 females aged 2 to 183 months (median 11 months). Twenty patients died while in the PICU. A PELOD-2 score (with lactate) cut-off ≥ 7 was determined by ROC curve, with sensitivity of 80% and specificity of 78%. The area under the curve (AUC) of PELOD-2 score (with lactate) was 84.8% (95%CI 74.7 to 95.9%). A PELOD-2 score (without lactate) ≥ 7 was the most optimum cut off based on its Youden index, it haD 70% of sensitivity and 80% of specificity. Conclusion PELOD-2 score ≥ 7 , with or without lactate component is the optimal cut-off for predicting life-threatening organ dysfunction in pediatric sepsis.